Analysis Health Information Systems Quality on the Effectiveness of Public Health Center Officers in Ambon City (Medico Legal Update, 2020)
Health information systems play a role in providing data, information and health indicators to support themanagement process will have an impact on increasing the effectiveness of work. The purpose of this researchis to know the quality influence of health information system that is seen from availability, timeliness, andrelevance to the effectiveness of employees of public health centers in Ambon City. The type of researchused is quantitative with cross sectional study design. The population in this study is all employees of theAmbon City Public Health Center amounting to 586 people, the withdrawal of samples with purposivetechnique obtained by 50 people. Collection of data through questionnaires. Data is analyzed by chi-squaretest. The results showed that the health information system of the availability aspect (P = 0.02), timely (P =0.01) and relevant (P = 0.04) significantly affected the effectiveness of healthcare personnel working in thePublic health center in Ambon city. It is hoped that the public health center in Ambon City can improve theexisting system so that the information produced is more quality.